Analysis of the assets, credits and deposits concentration within the Croatian banking system based on selected concentration indices - Mihovil Anelinović; Mihaela Milec; Ksenija Dumičić (Journal of Central Banking Theory and Practice, 2022)
This paper analyses the concentration of the banking system in Croatia and the impact of concentration on stability of the economic system as a whole over the period since 2002 to 2017. The level of concentration is usually related to the competitiveness of a particular sector, in this case the banking system, which affects the development and health of the country's entire economic system. The banking system, as the basis for the development of all other sectors of the economy, has been analysed here in the context of the concentration trend and efficiency in the selected time period using selected concentration indices: Concentration Ratio, Herfindahl-Hirschman Index, the Gini coefficient and the entropy measure using the variables of total assets of banks, loans granted, and received deposits. This research concludes that in the considered period of nearly 20 years, Croatia was among the EU countries with increased concentration level of the banking system.
Keywords: C43; D40; G21; L13; 330; concentration; banking system; concentration indices; banks' assets; credits; deposits; Herfindahl-Hirschman index; Gini coefficient